Metal oxide-containing coating composition and its uses
A coating composition using a silane compound, boron compound, and metal oxide powder with a specific organic solvent maintains transparency and drying properties under high temperature and humidity, addressing the limitations of existing coatings.
Patent Information
- Application Number
- JP2021007839
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-21
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-01-21
AI Technical Summary
Existing silicone-based near-infrared shielding coatings become cloudy under high temperature and high humidity conditions, limiting their use and requiring room temperature curing, and lower alcohols are needed for good drying properties.
A coating composition comprising an organic silane compound with an amino group, a boron compound, and a metal oxide powder, using an organic solvent with a primary hydroxyl group of 7 or more carbon atoms, which allows curing under high temperature and high humidity conditions while maintaining transparency and drying properties.
The composition provides a transparent coating film with near-infrared shielding ability and good drying properties even under high temperature and high humidity, suitable for applications like architecture, construction, and automotive windows.
Smart Images

Figure 0007617388000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal oxide-containing coating composition and its uses, and more specifically to a metal oxide-containing coating composition that can effectively block near-infrared rays and the like, and that provides good transparency of a coating film and good drying properties under high temperature and high humidity conditions, and its uses. [Background technology]
[0002] Silicone-based compositions containing alkoxysilanes, their polymers, or their hydrolysates can be cured at room temperature and are therefore used as coating agents for substrates such as glass, ceramics, and plastics. However, they are known to become cloudy under high temperature and high humidity conditions. Near infrared shielding coating agents are known that are prepared by blending, for example, inorganic near infrared shielding agents with silicone coating compositions, but in order to ensure the transparency of the coating film, it is necessary to avoid curing at high temperatures and high humidity, and the manner of use is practically limited to curing at room temperature. Also, in order to obtain good drying properties, it has been common to use lower alcohols with low boiling points. (See, for example, Patent Document 1.) [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2008-111048 A Summary of the Invention [Problem to be solved by the invention]
[0004] In view of the limitations of the above-mentioned conventional techniques, the problem that the present invention aims to solve is to provide a coating composition containing a metal oxide in order to obtain near-infrared shielding ability or the like, which gives a coating film with good transparency and good drying properties even when cured under high temperature and high humidity conditions such as those in summer, and uses of the coating composition. [Means for solving the problem]
[0005] As a result of intensive research, the present inventors have found that by using a specific alcohol-based solvent in a coating composition comprising a combination of an organosilane compound having an amino group with a specific structure, a boron compound having a specific structure, and a metal oxide powder, the coating film has good transparency and good drying properties even when cured under high temperature and high humidity conditions, and have completed the present invention. That is, the present invention provides: [1] A coating composition comprising the following components (a), (b), (c), and (d): (a) a silane compound containing an amino group represented by the following formula (I): R 4-n -Si-(OR') n -(I) (In the formula, R represents an amino group-containing organic group, R' represents a methyl group, an ethyl group, or a propyl group, and n represents an integer selected from 1 to 3.); (b) at least one boron compound selected from the group consisting of HBO and BO; (c) metal oxide powders; (d) an organic solvent; The present invention relates to the above coating composition, wherein the (d) organic solvent contains (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms.
[0006] Moreover, the following [2] to
[13] are each a preferred aspect or embodiment of the present invention. [2] (d1) The coating composition according to [1], wherein the boiling point of the organic solvent having a primary hydroxyl group having 7 or more carbon atoms is 180°C to 230°C. [3] (d1) The coating composition according to [1], wherein the boiling point of the organic solvent having a primary hydroxyl group having 7 or more carbon atoms is 180°C to 200°C. [4] The coating composition according to any one of [1] to [3], comprising (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms in an amount of 10 to 40 mass % of the total organic solvent (d). [5] (d1) The coating composition according to any one of [1] to [3], containing an organic solvent having a primary hydroxyl group having 7 or more carbon atoms in an amount of 5 to 25 mass % based on the total coating composition. [6] (d) At least a part of the organic solvent is a glycol ether solvent, [1] to [5], the coating composition of any one of [1] to [5]. [7] (c) The coating composition according to any one of [1] to [6], wherein the metal oxide powder contains diantimony pentoxide. [8] (c) The coating composition according to any one of [1] to [7], wherein the metal oxide powder has an average particle size of 10 to 100 nm. [9] A method for producing a coating layer, comprising the step of applying the coating composition according to any one of [1] to [8].
[10] The method for producing a coating layer according to [9], which forms a coating layer having a light transmittance of 5% or less at a wavelength of 2000 nm.
[11] The method for producing a coating layer according to [9] or
[10] , which forms a coating layer having a visible light transmittance of 80% or more.
[12] The method for producing a coating layer according to any one of [9] to
[11] , wherein a coating layer having a turbidity of 2.0% or less is formed.
[13] The method for producing a coating layer according to any one of [9] to
[12] , comprising forming a coating layer on a transparent substrate. Effect of the Invention
[0007] According to the present invention, it is possible to provide a metal oxide-containing coating composition which gives a coating film with good transparency and good drying properties even when cured under conditions ranging from room temperature to high temperature and high humidity conditions such as those in summer, and uses thereof. The coating composition provides a coating (coating film) obtained from the composition that has good near-infrared shielding function and transparency in visible light, and can form a good coating film even under high-temperature and high-humidity conditions. Therefore, the coating composition can be particularly suitably used in applications where the environment for coating film formation is restricted, such as architecture and construction applications where coating film formation in summer or outdoors is required, and in coatings for window materials for buildings, automobiles, etc., where the applied coating film will be used under high-temperature and high-humidity conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention relates to a coating composition comprising the following components (a), (b), (c) and (d): (a) a silane compound containing an amino group represented by the following formula (I): R 4-n -Si-(OR') n -(I) (In the formula, R represents an amino group-containing organic group, R' represents a methyl group, an ethyl group, or a propyl group, and n represents an integer selected from 1 to 3.) (b) at least one boron compound selected from the group consisting of H3BO3 and B2O3 (c) Metal oxide powder (d) Solvent
[0009] That is, the coating composition of the present invention contains the above-mentioned component (a) (a silane compound containing an amino group) and component (b) (a boron compound). The coating layer obtained by curing the coating composition of the present invention usually contains a compound at least partially containing a chemical structure obtained by reacting the components (a) and (b). In addition, the coating composition of the present invention may be in a state where the components (a) and (b) are partially reacted even before curing, and may contain a reaction product of the components (a) and (b) in part. The chemical structure obtained by reacting the above-mentioned component (a) (silane compound containing an amino group) and component (b) (boron compound), and optionally other components, often forms a polymer structure. Typically, the boron compound (b) acts as a crosslinking agent via the amino group in the silane compound containing an amino group (a), polymerizing these components to form a polymer structure having a constitutional unit derived from the silane compound containing an amino group (a) and a constitutional unit derived from the boron compound (b). Such a polymer structure has the preferable property of being able to stably disperse the metal oxide powder (c). In the coating composition of this preferred embodiment, the components (a) and (b) are combined in such a way that a reaction product having a polymer structure can be formed, typically under conditions of 10 to 50° C. That is, the reaction product has a polymer structure having a constituent unit derived from the component (a) and a constituent unit derived from the component (b). In this polymer structure, the ratio of the constituent unit derived from the component (a) to the constituent unit derived from the component (b) is preferably 0.02 moles or more of the constituent unit derived from the component (b) per mole of the constituent unit derived from the component (a).
[0010] In this embodiment, it is preferable that the (c) metal oxide powder is stably dispersed in a polymer structure having a structural unit derived from the (a) component and a structural unit derived from the (b) component.
[0011] (a) Silane compounds containing amino groups The component (a) used in the present invention is a silane compound containing an amino group and having a specific structure represented by the following formula: R 4-n -Si-(OR') n (In the formula, R represents an amino group-containing organic group, R' represents a methyl group, an ethyl group, or a propyl group, and n represents an integer selected from 1 to 3.)
[0012] Here, R represents an organic group containing an amino group, and examples thereof include, but are not limited to, monoaminomethyl, diaminomethyl, triaminomethyl, monoaminoethyl, diaminoethyl, triaminoethyl, monoaminopropyl, diaminopropyl, triaminopropyl, monoaminobutyl, diaminobutyl, triaminobutyl, and organic groups having an alkyl group or aryl group having a carbon number greater than these. γ-Aminopropyl and aminoethylaminopropyl are particularly preferred, and γ-aminopropyl is the most preferred.
[0013] In component (a), R' represents a methyl group, an ethyl group, or a propyl group, of which methyl and ethyl groups are preferred.
[0014] In the component (a), n represents an integer selected from 1 to 3. Of these, n is preferably 2 to 3, and n is particularly preferably 3. Therefore, as the component (a), γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and the like are particularly preferred.
[0015] (b) Boron compounds The component (b) used in the present invention is at least one boron compound selected from the group consisting of H3BO3 and B2O3. The component (b) is preferably H3BO3.
[0016] The amounts of component (a) and component (b) used in the reaction of the coating composition of the present embodiment are preferably in a ratio of 0.02 mol or more of component (b) per 1 mol of component (a), more preferably 0.02 mol to 8 mol of component (b) per 1 mol of component (a), and even more preferably 0.02 mol to 5 mol of component (b). By making the amount of component (b) 0.02 moles or more per mole of component (a), problems such as an excessively long time required for solidification, insufficient solidification, etc. can be effectively prevented. Also, by making the amount of component (b) 8 moles or less per mole of component (a), problems such as component (b) remaining undissolved in component (a) can be effectively prevented.
[0017] The mixing conditions (temperature, mixing time, mixing method, etc.) when reacting (a) a silane compound containing an amino group with (b) a boron compound can be appropriately selected. Under normal room temperature conditions, it becomes a transparent, viscous liquid and solidifies in a few minutes to a few tens of minutes. Since the solidification time and the viscosity and rigidity of the resulting reaction product differ depending on the proportion of the boron compound, it is preferable to adjust these conditions appropriately depending on the other components such as (c) metal oxide powder, the physical properties of the reaction product or coating to be obtained, and the intended use.
[0018] In the preferred embodiment, the reaction product of components (a) and (b) is preferably a reaction product obtained by reacting components (a) and (b) without a step of hydrolysis by adding water. In this case, since no step of hydrolysis by adding water is required, no complicated steps such as sol-gel formation are required, and the reaction product can be produced without a long time.
[0019] (c) Metal oxide powder The component (c) used in the present invention is a metal oxide powder. The metal oxide powder of component (c) is added with the intention of functioning as an infrared blocking material, and the addition of component (c) can effectively block infrared rays, particularly near-infrared rays.
[0020] The metal oxide powder of the component (c) in this embodiment may be a powder of a compound of a metal element and oxygen (the compound may contain elements other than the metal element and oxygen), and is not otherwise limited. For example, a powder of an oxide of at least one metal selected from Au, Ag, Ni, Cu, In, Sn, and Sb may be used. Preferably, ITO (indium tin oxide) and ATO (antimony oxide) are used. Dope The powder is at least one oxide selected from the group consisting of tin oxide.
[0021] In order for a coating to be transparent to visible light, it is desirable that the reflection and absorption of visible light is sufficiently small, and that scattering is as small as possible. Therefore, in order to reduce scattering, it is preferable that the coating be made of ultrafine particles with an average particle size of less than 1 / 2 the wavelength of visible light, i.e., less than 200 nm. Furthermore, in consideration of realizing low turbidity, the average particle size of the (c) metal oxide powder is preferably 10 to 100 nm, and particularly preferably 10 to 30 nm.
[0022] The transparency of the film obtained from the coating composition in visible light is affected by opacity (or turbidity, which is the proportion of scattered light components in the total transmitted light). If the turbidity exceeds 2%, the film feels cloudy, so in order to maintain transparency, it is preferable that the turbidity is 2% or less. To achieve such a turbidity of 2% or less, ITO (indium tin oxide) and ATO (antimony doped tin oxide) are used. D) When using particles with a refractive index of about 2, such as ultrafine particles, it is preferable to use particles dispersed with an average particle size of 100 nm or less. However, if the average particle size is too small, the transparency will increase but the near-infrared blocking ability may decrease, so in order to obtain a certain level of near-infrared blocking ability, it is preferable to keep the dispersed particle size at 10 nm or more while dispersing the ultrafine particles appropriately. Therefore, it is preferable to use the particles by adjusting the average particle size to an appropriate range, taking into consideration the balance between transparency in visible light and near-infrared blocking ability.
[0023] The amount of the metal oxide powder (c) used in the present invention is not particularly limited, but is preferably 1 to 30 parts by mass, more preferably 5 to 25 parts by mass, and even more preferably 10 to 20 parts by mass, based on 100 parts by mass of the entire coating composition.
[0024] In the present invention, in addition to the metal oxide powder of component (c), a near-infrared absorbing dye may be used in combination. In this case, the near-infrared absorbing dye is not particularly limited as long as it is a dye having near-infrared absorbing ability, and for example, at least one near-infrared absorbing dye selected from azo-based, aluminum-based, anthraquinone-based, cyanine-based, diimonium-based, diol metal complex-based, nosqualylium-based, and phthalocyanine-based near-infrared absorbing dyes can be mentioned. Among them, diimonium-based and phthalocyanine-based near-infrared absorbing dyes are preferred. Examples of such near-infrared absorbing dyes include [bis(4-t-butyl-1,2-dithiophenolate)copper-tetra-n-butylammonium] (BBT manufactured by Sumitomo Seika Chemicals), 1,1,5,5-tetrakis[4-(diethylamino)phenyl]-1,4-pentadiene-3-ylium-P-toluenesulfonate (Karenz IR-T manufactured by Showa Denko K.K.), and phthalocyanine compounds (TKR-2040 manufactured by Yamamoto Kasei Co., Ltd.).
[0025] In the present invention, in addition to the metal oxide powder of component (c), zinc oxide may be contained. Zinc oxide is an ultraviolet ray shielding material, and by adding zinc oxide, it is possible to effectively shield ultraviolet rays as well as infrared rays. The form of zinc oxide is not particularly limited, but from the viewpoint of maintaining the transmittance of visible light, it is preferably in the form of fine particles, and particularly preferably in the form of ultrafine particles. More specifically, ultrafine zinc oxide particles have an ultraviolet shielding function, but at the same time, in order to have good transmittance to visible light, it is preferable that the average particle diameter is 200 nm or less. By having an average particle diameter of 200 nm or less, it is possible to achieve excellent shielding performance against ultraviolet light while at the same time achieving sufficient transmittance to visible light. In addition, the dispersion stability is also good when dispersed in an acrylic dispersant, a phosphate ester dispersant, or the like, and the phenomenon of separation and precipitation of zinc oxide when left standing for a short period of time can be effectively suppressed.
[0026] (d) Organic Solvent The coating composition of the present invention contains a specific organic solvent (d) from the viewpoints of the transparency and drying properties of the coating film. More specifically, the organic solvent (d) used in the present invention contains an organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms. In the present invention, by using an organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms in the organic solvent (d), cloudiness and the like are effectively suppressed even when curing is performed under high temperature and high humidity conditions, and a coating film having excellent transparency can be formed.
[0027] The mechanism by which the use of the organic solvent (d1) having a primary hydroxyl group with 7 or more carbon atoms effectively suppresses cloudiness even under high temperature and high humidity conditions is not necessarily clear. However, it is presumed that there is some relationship between the use of the organic solvent (d1) having a primary hydroxyl group with 7 or more carbon atoms and the rate of the sol-gel reaction during coating film formation being appropriately controlled (the rate of the sol-gel reaction is not excessively high), etc. More specifically, the sol-gel reaction rate generally tends to be faster under high temperature and high humidity conditions, and also tends to be faster when a solvent with a small number of carbon atoms is used. However, when a solvent with a small number of carbon atoms is used under high temperature and high humidity conditions, the sol-gel reaction rate becomes excessive, which may result in the polymer particles formed by the reaction of the silane compound such as component (a) and the boron compound such as component (b) becoming large, or the dehydration reaction during the polycondensation reaction may not be able to keep up and water particles may be taken up by the coating film, resulting in the clouding. In contrast, when an organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms is used, the sol-gel reaction rate tends to be slower, and it is presumed that this suppresses the above-mentioned phenomenon that causes clouding even under high temperature and high humidity conditions, and also suppresses clouding.
[0028] The organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms is not particularly limited as long as it satisfies the conditions of having 7 or more carbon atoms and having a primary hydroxyl group. However, from the viewpoints of availability, appropriate boiling point, compatibility in the coating composition, etc., primary alcohols, glycol ethers, etc., which satisfy the conditions of having 7 or more carbon atoms, can be preferably used. The organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms preferably has 8 or more carbon atoms. There is no particular upper limit to the number of carbon atoms in the organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms, but from the viewpoint of obtaining an appropriate drying rate, it is preferably 12 or less. From the viewpoint of availability, the organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms preferably has an even number of carbon atoms, and particularly preferably has 8 or 10 carbon atoms.
[0029] Preferred examples of the organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms include, but are not limited to, 1-heptanol, 5-methyl-1-hexanol, 4-methyl-1-hexanol, 3-methyl-1-hexanol, 2-methyl-1-hexanol, 2-ethyl-1-pentanol, 1-octanol, 6-methyl-1-heptanol, 5-methyl-1-heptanol, 4-methyl-1-heptanol, 3-methyl-1-heptanol, 2-methyl-1-heptanol, 2-ethyl-1-hexanol, 1-nonanol, 1-decanol, 1-undecanol, 1-dodecanol, etc. It is particularly preferred to use 2-ethyl-1-hexanol, 1-octanol, 1-decanol, or diethylene glycol monobutyl ether (C8).
[0030] The boiling point of the organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms is not particularly limited, but is preferably 180°C to 230°C, and particularly preferably 180°C to 200°C. When the boiling point of the organic solvent (d1) is 180° C. or higher, the sol-gel reaction rate can be made more appropriate, and clouding and the like can be more effectively suppressed. When the boiling point of the organic solvent (d1) is 230° C. or lower, the drying speed can be made more appropriate.
[0031] In the present invention, all of the (d) organic solvents may be (d1) organic solvents having a primary hydroxyl group having 7 or more carbon atoms, or a part of the (d) organic solvents may be (d1) organic solvents having a primary hydroxyl group having 7 or more carbon atoms. (d1) An organic solvent having a primary hydroxyl group having 7 or more carbon atoms generally has a high boiling point, and if there is too much high-boiling point solvent, the drying rate may become slow. Therefore, it is preferable to use (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms in combination with (d2) an organic solvent other than (d1), for example, an organic solvent having a lower boiling point and a smaller carbon number than (d1). In this case, (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms preferably accounts for 10% to 40% by mass of all (d) organic solvents, and preferably accounts for 5% to 25% by mass of the entire coating composition. When the amount of (d1) the organic solvent having a primary hydroxyl group having 7 or more carbon atoms is 10 mass % or more of the total (d) organic solvents and / or 5 mass % or more of the total coating composition, the sol-gel reaction rate can be appropriately controlled and cloudiness and the like can be more effectively suppressed. When the amount of (d1) the organic solvent having a primary hydroxyl group having 7 or more carbon atoms is 40 mass % or less of the total (d) organic solvents and / or 25 mass % or less of the total coating composition, a sufficient drying rate can be obtained and the coating composition can be applied more efficiently.
[0032] There are no particular limitations on the organic solvent other than (d1) used as (d2), and any organic solvent that is miscible with (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms and that can dissolve or disperse the other components, i.e., components (a) to (c), can be used as appropriate.
[0033] From the viewpoint of affinity with the above-mentioned components, some of which have polar groups, and affinity with the substrate to be coated, it is preferable that the organic solvent (d2) other than (d1) is a so-called water-soluble organic solvent that has a certain polarity and is compatible with water. The water-soluble organic solvent preferably used as component (d2) is not particularly limited as long as it acts as a diluent and is water-soluble, but for example, alcohols can be preferably used. Among them, it is preferable to use alcohols having 2 to 6 carbon atoms as component (d2). Furthermore, (c) from the viewpoint of effectively dispersing the metal oxide powder, a glycol ether solvent such as methoxymethylbutanol (MMB) can also be used or used in combination.
[0034] The organic solvents (d1) and (d2) may be used alone or in combination of two or more. When using two or more in combination, a mixed solvent may be formed in advance and then used, or a part of each of the above components may be dissolved or dispersed in each of the two or more solvents and then combined. In particular, the solvent suitable for promoting the reaction between the above components (a) and (b) may differ from the solvent suitable for dispersing the above component (c), and in such a case, the latter embodiment is preferred.
[0035] The amount of (d) organic solvent used is not particularly limited, and may be appropriately set while taking into consideration the reaction efficiency between each component, including the components (a) and (b), the efficiency and workability in applying the coating, the quality of the resulting coating, and the like. Assuming a general use form such as near-infrared shielding coating, the amount of (d) organic solvent used is preferably 30 to 90 mass %, and more preferably 40 to 75 mass %, of the entire coating composition.
[0036] (e) Silane Compounds Containing Organic Functional Groups The coating composition of the present invention may preferably further contain (e) an organofunctional group-containing silane compound (excluding those corresponding to component (a)). Therefore, the polymeric substance that can be formed by the reaction of the coating composition of the present embodiment may have a structure in which the polymeric structure that is the reaction product of the above-mentioned components (a) and (b) is further modified with an organic functional group-containing silane compound (e). That is, an organic functional group-containing silane compound (component (e)) can be added during or after the reaction of components (a) and (b). By adding an organic functional group-containing silane compound (e), preferably a metal alkoxide, it is possible to appropriately adjust the polymer structure and increase the content of metal salt in the resulting reaction product, thereby further improving the mechanical properties, chemical properties, etc., and also to make the product in a viscous liquid state similar to that when component (e) is not used, so that the properties and physical properties of the coating can be appropriately adjusted depending on the application.
[0037] In the present invention, the (e) organic functional group-containing silane compound is preferably an alkoxy group-containing silane compound (hereinafter also referred to as "metal alkoxide") or an epoxy group-containing silane compound. From the viewpoint of realizing good substrate adhesion, an epoxy group-containing silane compound may be used. Metal alkoxides preferably used as component (e) exclude compounds that fall under component (a) above (silane compounds having a specific structure and containing an amino group), but no other restrictions apply. Compounds that are generally classified as metal alkoxides, i.e., compounds having at least one metal atom and at least one alkoxy group, can be used as metal alkoxides as long as they do not fall under component (a) above.
[0038] Metals of the metal alkoxide preferably used as the component (e) include, in addition to Si, Ta, Nb, Ti, Zr, Al, Ge, B, Na, Ga, Ce, V, Ta, P, Sb, etc., but are not limited thereto. Si, Ti, and Zr are preferable because of the ease of forming the alkoxide, and since the component (e) is preferably liquid, Si and Ti are particularly preferable from the viewpoint of realizing this. Examples of the alkoxide (alkoxy group) of the metal alkoxide include methoxy, ethoxy, propoxy, butoxy, and alkoxy groups having a carbon number of methoxy, ethoxy, propoxy, and butoxy, and more preferable are methoxy and ethoxy. Examples of particularly preferable metal alkoxides include tetramethoxysilane and tetraethoxysilane. The metal alkoxide may be a polymer, and for example, a pentamer of tetraethoxysilane can be suitably used. A monomer and a pentamer may be used in combination.
[0039] There are no particular limitations on the epoxy group-containing silane compound preferably used as component (e), but a compound having an alkoxy group such as methoxy, ethoxy, propoxy, or butoxy is preferred, and the epoxy group is preferably present in the form of an epoxy group-containing alkyl group such as a glycidoxypropyl group or an epoxycyclohexyl group. More specifically, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, etc. are particularly preferably used.
[0040] The amount of the (e) organic functional group-containing silane compound used is not particularly limited and can be appropriately set depending on the application and desired properties of the resulting coating, but it is preferable to use it in a ratio of 20 moles or less per mole of the (a) component. More preferably, it is 1 mole to 10 moles per mole of the (a) component. By using 1 mole or more of the (e) component per mole of the (a) component, the effects of adding the (e) component, such as improving the substrate adhesion and stably dispersing the (d) component (or the (c) component, if desired), can be fully exhibited. In addition, by using 10 moles or less of the (e) component, the occurrence of white turbidity can be effectively suppressed. When the component (e) is an alkoxy group-containing silane compound, the content thereof is preferably from 1 to 30 mass %, and particularly preferably from 5 to 20 mass %, based on the mass of the entire coating composition.
[0041] (g) Surfactants The coating composition of the present invention may further contain (g) a surfactant for the purposes of improving leveling properties for forming a smooth coating layer and improving adhesion to a substrate. The type of surfactant is not particularly limited, and can be appropriately selected depending on the application form of the coating, the affinity with other components, particularly the (d) organic solvent, etc. The surfactant may be any of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.
[0042] From the viewpoint of leveling property, penetrability, etc., it is particularly preferable to use a fluorine-based surfactant, a silicone-based surfactant, an alkyl ether-based surfactant, etc. Among them, from the viewpoint of leveling property, etc., it is preferable to use a silicone-based surfactant. Specific examples of preferred silicone surfactants include "VORASURF SZ-1919" manufactured by DOW and "BYK-307" manufactured by BYK Japan. Specific examples of preferred fluorine-based surfactants include the "Surflon" series manufactured by AGC Seimi Chemical Co., Ltd., the "Megafac" series manufactured by DIC Corporation, and the "Ftergent" series manufactured by NEOS Corporation.
[0043] There is no particular restriction on the amount of surfactant (g) added, and it can be appropriately set depending on the application form of the coating and the physical properties required after curing, etc. Assuming that the coating composition is generally used, the amount of the surfactant used is preferably 0.01 to 5.0 mass %, and particularly preferably 0.1 to 1.0 mass %, of the total coating composition.
[0044] Synthetic Resin The coating composition of the present invention may further contain a synthetic resin. That is, a synthetic resin may be added during or after the reaction of the components (a) and (b). By adding a synthetic resin, it is possible to impart crack prevention properties and the like to the resulting coating, and it is possible to improve the durability of the coating layer formed from the coating composition of the present invention.
[0045] The synthetic resin that can be used in this embodiment is not particularly limited, but examples thereof include acrylic resin, epoxy resin, polyester resin, amino resin, urethane resin, and furan resin, and synthetic resins having various degrees of polymerization (molecular weight) can be used. In addition, vinyl ester resin, epoxy acrylate, dipentaerythritol hexaacrylate, and the like can also be preferably used. Among them, it is preferable to use (f) epoxy resin from the viewpoints of properties as a resin such as strength, reactivity with other components, stability, and the like.
[0046] (f) Epoxy resin The coating composition of the present invention may contain, in addition to the essential components, (f) an epoxy resin. The (f) epoxy resin may be incorporated into the polymer structure composed of the above-mentioned (a) and (b) components during curing to form a part of the polymer structure, and may also crosslink the polymer structure to change the chemical structure and physical properties of the reaction product of the (a) and (b) components. By containing the (f) epoxy resin in this way, the coating composition of this embodiment can affect the chemical structure and physical properties of the reaction product that constitutes the cured coating, thereby controlling the reactivity, mechanical properties, etc. of the coating.
[0047] The epoxy resin (f) that can be preferably used in this embodiment is not particularly limited, and any resin classified as an epoxy resin in the art, that is, a thermosetting resin that can be cured by forming a crosslinked network with epoxy groups in a polymer structure, and epoxy resins having various degrees of polymerization (molecular weights) can be used. Among them, at least one epoxy resin selected from the group consisting of glycidyl ether type epoxy resins of bisphenol A or bisphenol F, hydrogenated bisphenol A type epoxy resins, glycidyl ester type epoxy resins, alicyclic epoxy resins, and polyglycol type epoxy resins can be preferably used.
[0048] (f) The amount of epoxy resin added is not particularly limited, and can be appropriately set depending on the application form of the coating and the physical properties required after curing, etc. Assuming that the coating composition is generally used, the amount of the epoxy resin (f) used is preferably 0.1 to 10 g, more preferably 0.5 to 5 g, per 1 g of the component (a). That is, if the amount of the epoxy resin (g) added is not too large, the decrease in hardness tends to be suppressed, and conversely, if it is not too small, chemical durability tends to be easily maintained.
[0049] Coating layer and method for producing same The coating composition of the present invention can be applied onto a substrate and cured to produce a coating layer. In general, in the method for producing the coating layer of this embodiment, the following components (a) and (b) are reacted in the presence of (c) an oxide powder in (d) an organic solvent: (a) A silane compound containing an amino group represented by the following formula (I): R 4-n -Si-(OR') n -(I) In the formula, R represents an amino group-containing organic group, R' represents a methyl group, an ethyl group, or a propyl group, and n represents an integer selected from 1 to 3. (b) at least one boron compound selected from the group consisting of H3BO3 and B2O3. Here, the (d) organic solvent contains (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms. In the above process, (e) an organic functional group-containing silane compound (excluding those corresponding to component (a)), (f) a synthetic resin such as an epoxy resin, (g) a surfactant, etc. may be used in combination. Here, the details of the above components (a) to (g) are the same as those explained above with respect to the coating composition of the present invention.
[0050] In the method for producing the coating layer of this embodiment, the coating composition of the present invention can be applied to the surface of the substrate by dipping, spray coating, roll coating, brush coating, or the like. The coating layer may be formed by one application, or by repeating two or more applications. When the coating layer is formed by repeating two or more applications, the coating composition may be cured after application and then further applied, or the coating may be repeated without curing, and the coating composition may be cured after all applications are completed. Heating is not essential for curing, but heating can shorten the curing time.
[0051] There is no particular limit to the amount of coating composition to be applied, but the coating amount is 2 The coating amount is preferably 1 g to 50 g, more preferably 2 g to 40 g, and particularly preferably 5.0 g or more per 100 cm2 of substrate area. 2 By setting the weight per unit area at 1 g or more, a coating layer of sufficient thickness can be formed.
[0052] There are no particular limitations on the thickness of the cured coating layer, and it can be set appropriately depending on the purpose of the coating, the required physical properties, the mode of use of the coated member, etc., but it is preferably 0.1 to 20 μm, and particularly preferably 0.5 to 10 μm. The coating layer after curing can achieve good near-infrared shielding ability, and for example, the light transmittance at a wavelength of 2000 nm can be preferably 5% or less, more preferably 4.5% or less. The coating layer after curing can achieve good visible light transmittance, for example, the visible light transmittance evaluated at a wavelength of 380 to 780 nm can be preferably 80% or more, more preferably 85% or more. The coating layer after curing can effectively suppress turbidity, and for example, the turbidity evaluated for visible light with a wavelength of 380 to 780 nm can be preferably 2.0% or less, more preferably 1.0% or less, and particularly preferably 0.5% or less.
[0053] In the present embodiment, the substrate on which the coating layer is formed is not particularly limited. From the viewpoint of effectively exerting the properties of the coating, such as near-infrared shielding ability, it is preferable that the coating layer is formed on a transparent substrate having high visible light transmittance. For example, it is particularly preferable to form the coating layer on a glass substrate, a transparent plastic substrate, or a transparent ceramic substrate, but is not limited to these.
[0054] The coating composition of the present invention provides a coating having a near-infrared shielding function, and has good transparency in visible light by effectively suppressing cloudiness, etc., and further enables the formation of a good coating film even under high temperature and high humidity conditions. Therefore, the coating composition of the present invention can be particularly suitably used in applications where the environment for coating film formation is restricted, such as architectural and construction applications where coating film formation in summer or outdoors is required, and in near-infrared shielding coatings for buildings and transport machinery such as automobiles, displays of electric and electronic equipment, etc., where the applied coating film is used under high temperature and high humidity conditions. EXAMPLES
[0055] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto in any way.
[0056] In the following Examples and Comparative Examples, the physical properties and characteristics were evaluated by the following methods. (Solution state) The coating compositions obtained in each of the Examples and Comparative Examples were visually observed to evaluate whether the fluidity of the composition as a liquid was maintained or whether a gel was formed. (Test piece preparation) The coating composition obtained in each Example / Comparative Example was applied to a glass plate with a roller at about 40 g / m 2 The coating was applied in an amount of 100 ml, and the coating was cured at 20°C and 60% relative humidity for 24 hours to prepare test pieces, which were then evaluated for coating appearance, near-infrared transmittance, and visible light transmittance according to the following methods. The tack-free time during curing was also evaluated according to the following methods. Test pieces were prepared in the same manner, except that the curing conditions were changed to 30°C and relative humidity 90%, and the coating appearance, near-infrared transmittance, visible light transmittance, and turbidity were evaluated according to the methods described below. (Coating appearance) The test pieces prepared as described above were visually observed, and the appearance of the coating was evaluated according to the following criteria. Transparent: There is no cloudiness or opacity, and the other side of the glass can be seen through. Cloudy: The glass is cloudy or opaque, making it impossible to see through to the other side. (Near infrared transmittance (%)) Using the test piece prepared according to the above-mentioned method, the transmittance of light having a wavelength of 2000 nm was measured with a spectrophotometer, and the near-infrared transmittance (%) was calculated. (Visible light transmittance (%)) Using the test piece prepared according to the above-mentioned method, the transmittance of light having a wavelength of 380 nm to 780 nm was measured with a spectrophotometer, and this was taken as the visible light transmittance (%). (Touch dry time (minutes)) The test pieces prepared according to the above-mentioned method were left in an atmosphere of 20° C. and 60% relative humidity, and the time required for the sample to no longer adhere to the fingertips was measured. (Turbidity) Using the test pieces prepared according to the above-mentioned method, the turbidity under visible light (380 to 780 nm) was measured with a spectrophotometer (manufactured by Hitachi High-Tech Science, model number: UH5700 and φ60 integrating sphere accessory).
[0057] Details of each component used in the following Examples / Comparative Examples are as follows: (a) Silane compound containing an amino group 1 γ-Aminopropyltriethoxysilane Shin-Etsu Chemical Co., Ltd., product name: KBE-903 (b) Boron compounds 1 Boric Acid (c) Metal oxide powder 1 ATO (tin-antimony oxide)-MMB (methoxymethylbutanol) dispersion MMB content: 69% Average particle size: 20nm Made by Mitsubishi Materials, product name: ATO-MMB dispersion (d1) Solvents having a primary hydroxyl group with 7 or more carbon atoms 2-Ethyl-1-hexanol (carbon number: 8), 1-octanol (carbon number: 8), diethylene glycol monobutyl ether (carbon number: 8), or 1-decanol (carbon number: 10) was used in the amounts shown in Table 1. (d2) Organic solvents other than (d1) Ethanol (carbon number: 2), 1-hexanol (carbon number: 6), 3-octanol (carbon number: 8), methoxymethylbutanol (carbon number: 6), diethylene glycol monomethyl ether (carbon number: 5), or 2-butoxyethyl acetate (carbon number: 8) were used in the amounts shown in Table 1. (e) Silane compound containing organic functional groups 1 Tetraethoxysilane pentamer (average) Colcoat Co., Ltd., product name: Ethyl Silicate 40 (e) Silane compound containing organic functional groups 2 Tetraethoxysilane Monomer Colcoat Co., Ltd., product name: Ethyl Silicate 28 (f) Epoxy resin 1 Hydrogenated bisphenol A epoxy resin Nagase ChemteX Corporation, product name: EX-252 (g) Surfactant 1 Silicone Surfactants Manufactured by DOW, product name: VORASURF SZ-1919
[0058] Example 1 The coating composition of Example 1 was prepared by mixing the components in the weight ratio shown in Table 1. At that time, the silane compounds ((a) silane compound 1 containing an amino group, (e) organic functional group-containing silane compound 1, and (e) organic functional group-containing silane compound 2) were sufficiently reacted with (b) boron compound 1, and then the other components were added. The solution stability of the obtained coating composition was evaluated according to the above method, and the coating film test pieces were prepared using the composition according to the above method and the properties were evaluated. The results are shown in Table 1.
[0059] (Examples 2 to 7, Comparative Examples 1 to 6) (d) Except for changing the type and amount of the solvent as component as shown in Table 1, coating compositions were prepared in the same manner as in Example 1, and the solution stability and coating properties were evaluated. The results are shown in Table 1.
[0060] [Table 1] [Industrial Applicability]
[0061] The coating composition of the present invention provides a coating (coating film) obtained from the composition, which has good near-infrared shielding function and visible light transparency, and can form a good coating film even under high temperature and high humidity conditions. Therefore, the coating composition can be particularly suitably used in applications where the environment for coating film formation is restricted, such as architectural and construction applications where coating film formation in summer or outdoors is required, and in coatings for windows of buildings and automobiles and displays of electric and electronic equipment, etc., where the applied coating film is used under high temperature and high humidity conditions, and has high applicability in various industrial fields, such as architecture, construction, transportation machinery such as automobiles, and electric and electronic equipment.
Claims
1. A coating composition comprising the following components (a), (b), (c), and (d): (a) a silane compound containing an amino group represented by the following formula (I): R 4-n -Si-(OR’) n -(I) (wherein R represents an amino group-containing organic group, R' represents a methyl group, an ethyl group, or a propyl group, and n represents an integer selected from 1 to 3); (b) H 3 B.O. 3 and B 2 O 3 at least one boron compound selected from the group consisting of: (c) metal oxide powder; (d) an organic solvent; And, (c) the metal oxide powder is indium tin oxide or antimony doped tin oxide particles having an average particle size of 200 nm or less; The above coating composition, wherein the organic solvent (d) contains (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms.
2. The coating composition according to claim 1, wherein the boiling point of the organic solvent (d1) having a primary hydroxyl group having 7 or more carbon atoms is 180°C to 230°C.
3. The coating composition according to claim 1, wherein (d1) the organic solvent having a primary hydroxyl group having 7 or more carbon atoms has a boiling point of 180°C to 200°C.
4. 4. The coating composition according to claim 1, comprising (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms in an amount of 10 to 40 mass % of the total organic solvents (d).
5. The coating composition according to any one of claims 1 to 3, comprising (d1) an organic solvent having a primary hydroxyl group having 7 or more carbon atoms in an amount of 5 to 25 mass% of the total coating composition.
6. 6. The coating composition according to claim 1, wherein at least a portion of the (d) organic solvent is a glycol ether solvent.
7. The coating composition according to any one of claims 1 to 6, wherein the average particle size of the (c) metal oxide powder is 10 to 100 nm.
8. A method for producing a coating layer, comprising the step of applying the coating composition according to any one of claims 1 to 7.
9. The method for producing a coating layer according to claim 8, wherein a coating layer having a light transmittance of 5% or less at a wavelength of 2000 nm is formed.
10. The method for producing a coating layer according to claim 8 or 9, wherein a coating layer having a visible light transmittance of 80% or more is formed.
11. The method for producing a coating layer according to any one of claims 8 to 10, wherein a coating layer having a turbidity of 2.0% or less is formed.
12. The method for producing a coating layer according to claim 8 , further comprising forming a coating layer on a transparent substrate.
Citation Information
Patent Citations
Coating liquid for forming sun radiation shielding film, sun radiation shielding film and base material having sun radiation shielding function
JP2008101111A
Near-infrared-shielding coating composition
JP2008111048A
Sheet glass with ultraviolet shielding coating and manufacturing method therefor
JP2018080106A